A submarine arrangement design program based on the expert system and the multistage optimization. (August 2016) - Kim, Ki-Su; Roh, Myung-Il
Highlights: An arrangement method of submarine compartments and equipment based on an expert system and a multistage optimization is proposed. An optimization method that can yield a better arrangement design of a submarine is proposed. We develop a prototype program based on an arrangement template model, an expert system module, and an optimization module. We apply the program to a problem of a small submarine. Abstract: The arrangement design of a submarine depends on the data of the parent ships and the knowledge of experts. Some delay in design can occur when data or experts are absent. An arrangement design problem of a submarine can also be difficult to solve due to the number of compartments and equipment placed in the limited space, as well as the numerous potential alternatives for the arrangement design. Thus, a compelling need arises to accumulate data regarding the parent ships, the knowledge of experts, and design rules as a systematic structure, increasing the demand for optimization of the arrangement design. In this study, we proposed an arrangement method of the submarine compartments and equipment based on an expert system and a multistage optimization. For this task, we used a template model for the arrangement design of a submarine proposed by the authors in the previous study to store the arrangement data. We also improved and used an expert system that can systematically computerize the knowledge of experts, previously developed by the authors. Then, we proposed an optimization method that can yield a better arrangement design after formulating a submarine arrangement problem as an optimization problem, solving it with the use of an efficient optimization algorithm. To evaluate the applicability of the proposed method, we developed a prototype program consisting of an arrangement template model, an expert system module, and an optimization module. Finally, we applied the developed program to a problem with regard to the arrangement design of a small submarine. The results showed that the developed program can be used as a new tool for the arrangement design of a submarine.